Reimagining Literacy Practices in Indonesian Classrooms: Translanguaging Pedagogies in Multilingual Contexts - Wulandari, Rini; Hidayat, Ahmad; Amalia, Rika; Fadli, Muhammad (Jurnal Tahuri, 2023)
This study reimagines classroom literacy practices in Indonesian multilingual contexts by examining how translanguaging, dynamic alternation between languages to build meaning, can function as a pedagogical strategy that bridges the gap between students’ home literacies and the monolingual practices of formal schooling. Employing a qualitative multiple case study with light classroom ethnography, the research was conducted in five secondary schools in Garut, West Java. Data were collected through classroom observations involving reading, text discussions, and writing activities; semi-structured interviews with teachers and students; and analysis of instructional documents. Discourse analysis was used to identify the forms and functions of translanguaging in classroom interaction, while thematic analysis explored participants’ perceptions and experiences. The findings reveal that translanguaging naturally emerges in various classroom interactions, particularly during group discussions and concept explanations, enhancing students’ conceptual understanding, encouraging active participation, and bridging home–school literacy practices. Teachers and students flexibly used Sundanese, Indonesian, and English to construct more inclusive meanings, yet curricular policies that emphasize formal Indonesian remain a key constraint. This study offers new empirical evidence of translanguaging in Indonesian secondary literacy classrooms and proposes a conceptual model grounded in local practices, contributing to educational, linguistic, and applied language studies by highlighting the need for pedagogies that are linguistically responsive and socially contextualized.